PENERAPAN SISTEM PENDUKUNG KEPUTUSAN BERBASIS WEB UNTUK MENENTUKAN PRIORITAS LAYANAN KESEHATAN HOME VISIT LANSIA DI PUSKESMAS BALARAJA - Rika; Suwarno, Joko (Information Technology Education Department, 2025)
Home visit services at Puskesmas Balaraja often face challenges in determining the priority of visits, as the number of elderly patients requiring services exceeds the available medical staff capacity. To address this issue, this study designs a web-based decision support system using the Multi-Objective Optimization on the Basis of Rational Analysis (MOORA) method. The MOORA method is applied to evaluate alternatives based on several criteria, namely age, medical history, and level of independence. The calculation process involves constructing a decision matrix, determining sub-criteria values, normalization, and optimization to generate priority rankings. The results show that from 100 elderly patient data, the highest score was achieved by Munah, who ranked first in visit priority. The implementation of the MOORA method has proven effective in supporting systematic decision-making, reducing the time required for determining visit priorities from two days to approximately 15 minutes, and producing more accurate decisions that meet the healthcare needs of elderly home visits at Puskesmas Balaraja.